Drought effects on montane grasslands nullify benefits of advanced flowering phenology due to warming. Issue 7 (21st July 2021) - Schuchardt, Max A.; Berauer, Bernd J.; von Heßberg, Andreas; Wilfahrt, Peter; Jentsch, Anke
Abstract: Warming due to climate change is generally expected to lengthen the growing season in areas of seasonal climate and to advance plant phenology, particularly the onset of leafing and flowering. However, a reduction in aboveground biomass production and reproductive output may occur when warming is accompanied by drought that crosses critical water deficit thresholds. Tracking warmer temperatures has been shown to be species‐specific with unknown impacts on community composition and productivity. The variability in species' ability to leverage earlier leaf unfolding and flowering into increased aboveground net primary production (ANPP) or increased investments into reproductive organs has heretofore been poorly explored. We tested whether phenological sensitivity to temperature, as a result of experimental warming, directly translated into increased plant performance, as measured by ANPP and flower abundance. In order to experimentally simulate climate warming, we translocated a total of 45 intact soil–plant communities downslope along an elevational gradient of 900 m within the European Alps from 1260 to 350 m asl and weekly recorded flower abundance and total green cover as well as cumulative biomass production at peak growing season. We found that advanced phenology at lower elevations was related to increased reproductive performance and conditional on whether they experienced drought stress. While a temperature increase of +1K had positive effects on the amount of reproductive organs for species with accelerated phenology, temperature increase going along with drier conditions resulted in plants being unable to sustain early investment in reproduction as measured by flower abundance. This finding highlights that the interaction of two climate change drivers, warming and drought, can push communities' past resistance thresholds. Moreover, we detected biotic competition mechanisms and shifts toward forb‐depressed states with graminoids best taking advantage of experimentally altered increased temperature and reduced precipitation. Our results suggest that while species may track warmer future climates, concurrent drought events post a high risk for failure of temperature‐driven improvement of reproductive performance and biomass production in the European Alps.